A Water Molecule Triggers Guest Exchange at a Mono‐Zinc Centre Confined in a Biomimetic Calixarene Pocket: A Model for Understanding Ligand Stability in Zn Proteins. Issue 55 (16th September 2021) - Brunetti, Emilio; Marcelis, Lionel; Zhurkin, Fedor E.; Luhmer, Michel; Jabin, Ivan; Reinaud, Olivia; Bartik, Kristin
Abstract: Invited for the cover of this issue are Kristin Bartik, Olivia Reinaud and co‐workers at the Université libre de Bruxelles and Université Paris Descartes. The image depicts a Zn protein and highlights the role that a single water molecule can play in catalysing ligand exchange. Read the full text of the article at 10.1002/chem.202102184 . Abstract : " This four‐step process explains the inertness of biological Zn centers where a five‐coordinate state is precluded ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13730 ff. (DOI: 10.1002/chem.202102184 ).